2016
DOI: 10.1145/2911982
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Phones as Amplifiers of Social Inequality among Rural Kenyan Women

Abstract: This article provides a detailed analysis of rural Kenyan women and their interactions with the products and services of Safaricom Ltd., Kenya's dominant mobile network provider. The amplification theory of technology offers a framework for analyzing our data, and we find that differential motivation and capacity are mechanisms that appear to benefit the network provider, while disadvantaging rural mobile phone owners. In particular, the design of Safaricom's airtime scratch cards and mobile services does not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…Fisher et al [22] studied how Syrian youths use connected technology to help others in the Za'atari refugee camp in Jordan, whilst Maitland and Xu [37] found that a large majority (86%) of refugees in the same camp owned a mobile phone. Talhouk et al [50,51] 57]. However, unlike the focus of this cannon of literature that explores the role of mobile technology either during the refugee journey or in the old home country, the focus of our paper differs from this body of work as it looks at mobile phone use in the new country, at a time of changing precarity and where the pressures of old and new homes collide.…”
Section: Mobile Phone Use In Refugee Communitiesmentioning
confidence: 99%
“…Fisher et al [22] studied how Syrian youths use connected technology to help others in the Za'atari refugee camp in Jordan, whilst Maitland and Xu [37] found that a large majority (86%) of refugees in the same camp owned a mobile phone. Talhouk et al [50,51] 57]. However, unlike the focus of this cannon of literature that explores the role of mobile technology either during the refugee journey or in the old home country, the focus of our paper differs from this body of work as it looks at mobile phone use in the new country, at a time of changing precarity and where the pressures of old and new homes collide.…”
Section: Mobile Phone Use In Refugee Communitiesmentioning
confidence: 99%
“…Existing evidence, even though debated, show how the adoption and use of DTs (eg, mobile financial services, m‐Health, and e‐Agriculture) positively contribute to the transformation of societies (Aker & Ksoll, ). On the contrary, other studies, eg, Wyche, Simiyu, and Othieno (), show that the adoption and use of DTs in societies have, to some extent, led to the undoing of development in rural communities, for example, by exacerbating social inequalities. These contrasting technology affordances are the proponents of the social determinism approach, which argues that DTs' impacts on societies are not predetermined; thus, technologies can have either desired or undesired impact depending on how societies appropriate the DTs (Luna‐Reyes & Gil‐Garcia, ).…”
Section: Introductionmentioning
confidence: 95%
“…There is also a paper-by Wyche, Simiyu and Otheno [60]-that examines the mobile phone skills of Kenyans, but, as we will explain, this paper might be more about step 3 than about step 2. Specifically, Wyche et al rely on the amplification theory of technology-which holds that technology can amplify existing social inequalities-to study how rural Kenyan women interact with the products and services of Safaricom.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%